Lightweight privacy preservation for secondary users in cognitive radio networks. (15th July 2020) - Zeng, Yali; Xu, Li; Yang, Xu; Yi, Xun; Khalil, Ibrahim
Abstract: Cognitive radio is emerging as a technology to alleviate spectrum shortage and to improve spectrum utilization. In database-driven cognitive radio networks (CRNs), secondary users (SUs) must provide their locations to the database to enable channel allocation, which results in severe privacy violation. As SUs are usually energy-constrained or fast-moving, how to provide efficient channel allocation solutions for SUs while guaranteeing security and privacy becomes a main challenge in database-driven CRNs. In this paper, we propose a lightweight privacy-preserving scheme to protect the privacy of SUs and to allocate channels efficiently with the aid of base stations (BSs). In order to save the energy of SUs and to reduce the delay of channel allocation, only lightweight operations are required to achieve authentication and privacy preservation of SUs. For further improving the efficiency of channel allocation, the database periodically predicts and pre-allocates channels to BSs for the purpose of allocating channels to SUs locally. We perform the security verification using the automated protocol verifier tool Proverif to show that our scheme resists various attacks. Performance analysis reveals that our scheme significantly reduces computation and communication cost of SUs and incurs the shortest delay in channel allocation.